Manajemen Pelatihan Tata Rias Pengantin Dalam Meningkatkan Kemandirian Berwirausaha di Kampung Cidadap, Kelurahan Tinggar, Kecamatan Curug, Kota Serang-Banten - Siti Nurholisoh; Syadeli Hanafi; Dadan Darmawan (Peneliti.net, 2023)
This study aims to describe (1) the management of bridal make-up training in increasing entrepreneurial independence in Cidadap Village (2) the results of entrepreneurial independence after attending bridal make-up training in Cidadap Village. The research method used is descriptive method with a qualitative approach. Data collection techniques used are observation, interviews, and documentation. The data sources in this study consisted of 12 people, namely 1 training organizer, 1 training instructor, and 10 bridal makeup training participants in Cidadap Village. The results of the study show that: (1) the stages of bridal makeup training management consist of training planning, training implementation, and training evaluation; the training activities have been carried out optimally with the results of the evaluation of the bridal make-up training indicated significantly, such as some participants have become independent entrepreneurs in this field of make-up. (2) the result of self-employment independence after attending this bridal make-up training is that participants gain new understanding and skills in the field of bridal make-up by utilizing their expertise as well as training tools and materials obtained during the cosmetology training activities as initial capital to become independent business actors opening services make-up at home like make-up for elementary school release, art stage, etc.